Quadratus lumborum block in chronic pain after abdominal hernia repair: case report - Carvalho,Rita (2017)
Abstract Background and objectives: The quadratus lumborum blockade was described by R. Blanco in its two approaches (I and II). The local anesthetic deposition in this location can provide blockade to T6-L1 dermatomes. We performed this fascia blockade guided by ultrasound for treating a chronic neuropathic pain in the abdominal wall. Case report: Male patient, 61 years old, 83 kg, with a history of thrombocytopenia due to alcoholic cirrhosis, among others; had chronic pain in the abdominal wall after multiple abdominal hernia repairs in the last year and a half, with poor response to treatment with neuromodulators and opioids. On clinical examination, he revealed a neuropathic pain, with prevalence of allodynia to touch, covering the entire anterior abdominal wall, from T7 to T12 dermatomes. We opted for a quadratus lumborum block type II, guided by ultrasound, with administration of 0.2% ropivacaine (25 mL) and depot (vial) methylprednisolone (20 mg) on each side. The procedure gave immediate relief of symptoms and, after six months, the patient still had a significant reduction in allodynia without compromising the quality of life. Conclusions: We consider that performing the quadratus lumborum block type II was an important analgesic option in the treatment of a patient with chronic pain after abdominal hernia repair, emphasizing the effects of local anesthetic spread to the thoracic paravertebral space. The technique has proven to be safe and well tolerated. The publication of more clinical cases reporting the effectiveness of this blockade for chronic pain is desirable.